Metal‐Free C−H Borylation of N‐Heteroarenes by Boron Trifluoride. Issue 61 (29th September 2020) - Iashin, Vladimir; Berta, Dénes; Chernichenko, Konstantin; Nieger, Martin; Moslova, Karina; Pápai, Imre; Repo, Timo
Abstract: Organoboron compounds are essential reagents in modern C−C coupling reactions. Their synthesis via catalytic C−H borylation by main group elements is emerging as a powerful tool alternative to transition metal based catalysis. Herein, a straightforward metal‐free synthesis of aryldifluoroboranes from BF3 and heteroarenes is reported. The reaction is assisted by sterically hindered amines and catalytic amounts of thioureas. According to computational studies the reaction proceeds via frustrated Lewis pair (FLP) mechanism. The obtained aryldifluoroboranes are further stabilized against destructive protodeborylation by converting them to the corresponding air stable tetramethylammonium organotrifluoroborates. Abstract : C−H activation : Indoles, pyrroles and indolenines undergo C−H borylation by boron trifluoride with assistance of base and thiourea additives.